Back Cover: Microkinetic Modeling of Benzyl Alcohol Oxidation on Carbon‐Supported Palladium Nanoparticles (ChemCatChem 15/2016). Issue 15 (8th August 2016) - Savara, Aditya; Rossetti, Ilenia; Chan‐Thaw, Carine E.; Prati, Laura; Villa, Alberto
Abstract : The Cover shows a micro‐kinetic model being applied to benzylic alcohol oxidation over metal nanoparticles. In their new Full Paper, A. Savara et al. report the first micro‐kinetic modeling of liquid phase benzylic alcohol oxidation over transition metal nanoparticles. The micro‐kinetic model was applied to palladium nanoparticles and enabled applying the concept of a sticking coefficient in solution. The kinetic simulations were able to reproduce the 18 trends observed in the responses of the six products when varying the alcohol concentration, oxygen pressure, and temperature. The mechanism used was based on surface science knowledge and an earlier study published in ChemCatChem . More information can be found in the Full Paper by A. Savara et al. et al. onpage 2482 in Issue 15, 2016 (DOI:10.1002/cctc.201600368 ).